Shensong Yangxin Protects Against Metabolic Syndrome-Induced Ventricular Arrhythmias by Inhibiting Electrical Remodeling - Yang, Hong-Jie; Kong, Bin; Shuai, Wei; Zhang, Jing-jing; Huang, He (Frontiers in Pharmacology, 2020)
Shensong Yangxin (SSYX) is a traditional Chinese medicine, which has been proven to improve the clinical symptoms of arrhythmia. However, the role of SSYX in metabolic syndrome (MetS)-induced electrical remodeling remains to be fully elucidated. Here, we sought to clarify whether SSYX can alter the electrophysiological remodeling of cardiac myocytes from MetS rats by regulating transient outward potassium current (Ito) and calcium current (ICa-L). Male Wistar rats were subjected to 16 weeks of high-carbohydrate, high-fat to produce a MetS model group. SSYX (0.4g/kg) was administrated by daily gavage 8 weeks following high-carbohydrate, high-fat for 8 weeks. In vivo electrophysiological study was performed to evaluated ventricular arrhythmias (VA) vulnerability and electrophysiological properties. The potential electrical mechanisms were estimated by whole-cell patch-clamp and molecular analysis. The H9C2 cells were used to verify the protective role of SSYX in vitro. After 16-week high-carbohydrate, high-fat feeding, MetS model rats showed increased body weight (BW), blood pressure (BP), blood sugar (BS), heart rate (HR) and heart weights to tibia length (HW/TL) ratio. Furthermore, MetS rats depicted increased VA inducibility, shortened effective refractory period (ERP) and prolonged action potential duration (APD). Lower ICa-L and Ito current densities were observed in MetS rats than CTL rats. Additionally, MetS rats exhibited significantly increased Cx43 expression, cardiac fibrosis and decreased protein levels of Cav1.2, Kv4.2, Kv4.3 than CTL group. As expected, these MetS-induced effects above were reversed when SSYX was administrated. Mechanistically, SSYX administrated significantly down-regulated the TLR4/MyD88/CaMKII signaling pathway both in vivo and in vitro. Collectively, our data indicated that the electrical remodeling induced by MetS contributed to the increased VA susceptibility. SSYX protects against MetS-induced VA by inhibiting electrical remodeling through TLR4/MyD88/CaMKII signaling pathway.